Refugees’ integration and emotional distress over the course of 9 months - Potter, Flurina; Dohrmann, Katalin; Rockstroh, Brigitte; Crombach, Anselm (Frontiers in Psychology, 2024)
Background High prevalence rates of mental disorders are reported in refugees due to experiencing substantial pre-, peri-, and post-migration stress. While long-term studies indicated that emotional distress of refugees either stagnates or ameliorates over time, long-term research on refugees’ integration and its’ interaction with emotional distress is limited. The examined long-term predictors for refugees’ emotional distress and integration in this study were, amongst others, severe physical abuse in childhood, residence status and length of stay. Methods The sample included 46 refugees, 91.3% male, mean age 20.8 years. Trained psychologists screened for emotional distress with the use of the Refugee Health Screener in a semi-structured interview. Integration progress was screened using the Integration Index with the subdimensions psychological, economic, political, social, linguistic and navigational integration. Longitudinal differences for emotional distress and integration sub-dimensions were evaluated by sign tests and t-tests. The longitudinal course of integration was evaluated with a Mixed ANOVA. Further, two hierarchical regression analyses were performed to analyze longitudinal predictors of emotional distress and integration. Results Overall, emotional distress decreased, and integration increased over time. In particular, the sub-dimensions of social, economic, and linguistic integration increased significantly over time. Two regression analyses determined significant predictors of (a) emotional distresst1 (adjusted R2 = 0.46): psychotherapy (ß = 0.35, p = 0.020), emotional distresst0 (ß = 0.34, p = 0.031), and integrationt0 (ß = −0.29, p = 0.043), and one significant predictor of (b) integrationt1 (adjusted R2 = 0.70): integrationt0 (ß = 0.89, p < 0.001). Conclusion This is the first study to longitudinally examine the Integration Index with all subdimensions. Over the course of 9 months refugees’ overall integration, and the sub-dimensions of social, economic, and linguistic integration increased. Whilst the emotional distress of initially highly distressed refugees ameliorated over the course of nine months, their symptom severity remained clinically significant. Results emphasize the importance of early integration for the long-term development of mental health and integration in refugees. Refugees’ emotional distress and integration are intertwined and need to be addressed promptly after refugees’ entry into the host country.